Kerja Sama Dalam Memberantas Tindak Kejahatan Internasional (Indonesia-Swiss) - Dwi Aprillia; Mirnawati Munthe; Tamaulina Br.Sembiring (PT. ALHAFI BERKAH INDONESIA, 2024)
International crimes are crimes that cause unrest in the international community or acts that violate fundamental interests protected by international law. Every country definitely has problems, problems in the form of crime being one of them. This crime problem can occur not only within the scope of the country, but can occur outside the scope of the country or is called an international crime. To overcome or prevent the occurrence of international crimes, an agreement is made between two countries, namely the International Agreement. Such as international crimes that occurred between Indonesia and Switzerland, resulting in an international agreement using a Reciprocal Law Agreement (MLA).